THE IMPACT OF PARENTAL DIVORCE ON THE SOCIO-EMOTIONAL DEVELOPMENT OF EARLY CHILDHOOD IN MOYOT HALL, MOYOT VILLAGE, SAKRA DISTRICT, EAST LOMBOK REGENCY - Zikriatul Isnaini (Sinar Lima, 2025)
This study found that many children are victims of parental divorce which has an impact on the social and emotional well-being of early childhood children, this causes children to be neglected and even children are less able to concentrate on their studies, even as a result of their parents' divorce, children sometimes appear gloomy, some are also a bit naughty due to a lack of attention from their parents which has an impact on social and emotional well-being. Therefore, the researcher is interested in conducting a study entitled: